Characterization of the immunomodulatory protein isolated from guduchi (Tinospora cordifolia) churna, an ayurvedic rejuvenator - Raju R. Shruthi; Ivan Aranha; Yeldur P. Venkatesh (World Scientific Publishing, 2023)
Objective: Guduchi [Tinospora cordifolia (Willd.) f. and Thoms.], a rasayana (rejuvenator) in the traditional system of Indian medicine (Ayurveda), is known for its diverse bioactivities. The aim of this study was to isolate the immunomodulatory protein (ImP) from commercial guduchi churna (stem powder) and characterize it. Methods: Guduchi churna extract following 80% ammonium sulfate precipitation was chromatographed on Q-Sepharose. Purified guduchi ImP was evaluated for its lymphoproliferative and macrophage activation properties, structural relatedness to certain plant lectins, amino acid composition, stability to trypsin, and N-terminal sequencing. Results: The purified protein, obtained in a yield of 140[Formula: see text]mg/100[Formula: see text]g guduchi churna, showed a molecular mass of [Formula: see text] kDa by SDS-PAGE. Guduchi ImP (10 [Formula: see text]g) showed seven-fold increase over control in mitogenic activity of murine splenocytes, and a four-fold increase over control in nitric oxide (NO) release from murine peritoneal exudates cells (PECs). These activities were abolished in pronase-treated guduchi ImP. Guduchi ImP does not agglutinate rabbit erythrocytes. Rabbit antiserum to guduchi stem ImP strongly reacted with purified guduchi ImP, and did not recognize common plant lectins (concanavalin A (Con A), poke weed mitogen (PWM) and garlic lectin). Amino acid composition of guduchi ImP shows high content of acidic amino acids, serine (12.4%) and cysteine (10.2%); guduchi ImP is highly stable to trypsin and has a blocked N-terminus. Conclusion: Guduchi ImP is an acidic, non-lectin ImP with a high content of serine and cysteine, and appears to have an immense potential for future structural, immunological, and therapeutic studies.